Association of Glycated Hemoglobin Level and Postoperative Complications in General Surgical Procedures - Farid, Nadir; Anwar, Muhammad Rizwan; Nazir, Muhammad Tariq; Bakhtiar, Nasir; Afzal, Muhammad; Ahmed Babar, Shahzada Amir (Journal of Neonatal Surgery, 2025)
Background: Elevated glycated hemoglobin (HbA1c) levels have been identified as a significant risk factor for postoperative complications. Understanding the relationship between preoperative HbA1c and surgical outcomes is critical for improving perioperative care in diabetic patients. Objective: To evaluate the association between HbA1c levels and the incidence of postoperative complications in diabetic patients undergoing general surgical procedures. Material and Methods: This cross-sectional study was conducted at the DG Khan Medical College, from June 2023 to June 2024. A total of 341 diabetic patients who underwent elective and emergency surgical procedures were included. Data were collected on patient demographics, comorbidities, preoperative HbA1c levels, and postoperative complications. Glycemic control was classified as good (HbA1c ≤7%) or poor (HbA1c >7%). Statistical analyses were performed using chi-square tests, with significance set at p < 0.05. Results: The mean age of the patients was 49.54±18.77 years, with a mean BMI of 26.72±4.97 kg/m² and mean HbA1c level of 8.75±1.94%. Postoperative complications were significantly higher in patients with poor glycemic control (64.8%) compared to those with good glycemic control (20.0%) (p < 0.001). No statistically significant associations were observed with age, sex, obesity status, duration of diabetes, or smoking status. Conclusion: Poor preoperative glycemic control, as indicated by elevated HbA1c levels, is strongly associated with an increased risk of postoperative complications in diabetic patients. Effective glycemic management prior to surgery is crucial for optimizing outcomes.